2004
DOI: 10.1002/art.20302
|View full text |Cite
|
Sign up to set email alerts
|

Local activation of STAT‐1 and STAT‐3 in the inflamed synovium during zymosan‐induced arthritis: Exacerbation of joint inflammation in STAT‐1 gene–knockout mice

Abstract: Objective. STAT proteins play an important role in cytokine signaling. Some investigators have reported preferential activation of STAT-1, and others have reported preferential activation of STAT-3, in response to endogenous interleukin-6 (IL-6), in patients with rheumatoid arthritis. The present study was undertaken to investigate synovial STAT-1 and STAT-3 activation in an experimental animal model of arthritis.Methods. Zymosan was injected intraarticularly into naive wild-type (WT), IL-6 ؊/؊ , and STAT-1 ؊/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 41 publications
1
61
0
Order By: Relevance
“…At high doses ZA is recognized to trigger a massive neutrophil-dominated influx of leukocytes when injected into closed spaces in vivo. 29,30 Reducing the dose of ZA avoided this response but even at the lower range of concentrations used in the dose-response assay there was still evidence of a dose-dependent inflammatory effect. Systemically, serum TNF-a levels at early time points were elevated in high ZA dose as compared to low-dose mice and controls.…”
Section: Discussionmentioning
confidence: 99%
“…At high doses ZA is recognized to trigger a massive neutrophil-dominated influx of leukocytes when injected into closed spaces in vivo. 29,30 Reducing the dose of ZA avoided this response but even at the lower range of concentrations used in the dose-response assay there was still evidence of a dose-dependent inflammatory effect. Systemically, serum TNF-a levels at early time points were elevated in high ZA dose as compared to low-dose mice and controls.…”
Section: Discussionmentioning
confidence: 99%
“…The role of SOCS proteins in mediating inhibition of cytokine and growth factor responses makes the SOCS proteins prime candidates for regulating chondrocyte function during growth and joint diseases. During joint inflammation and after in vivo IL-1 exposure, SOCS-3 is highly expressed in both synovial tissue and chondrocytes (10). In a recent study, we demonstrated that adenoviral overexpression of SOCS-3 caused IGF-1 nonresponsiveness in a murine chondrocyte cell line (6).…”
mentioning
confidence: 87%
“…Alternatively, STAT-1 induces growth arrest and promotes apoptosis in several cell types, including lymphocytes and synovial fibroblasts (30)(31)(32)(33). These functions suggest a protective role for STAT-1 in arthritis, and this possibility is supported by the elevated expression of the STAT-1 proapoptotic target gene caspase-1 in RA synovium (10), and by evidence that STAT-1 deficiency results in exacerbation of experimental arthritis (34). Thus, STAT-1 may have both pathogenic and protective roles in RA synovitis, depending on the cell type and possibly on the stage of disease and the inflammatory microenvironment.…”
Section: Stat Function In Ra Synovitis: Pathogenic or Protective?mentioning
confidence: 99%